The Effect Of Earnings Per Share (EPS), Current Ratio (CR), And Return On Equity (ROE) On Pt Unilever Indonesia Tbk's Stock Price - Mufidah, Euis Nurul; Pratiwi, Aliah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study aims to examine the effect of Earning Per Share, Current Ratio, and Return On Equity on stock prices at PT Unilever Indonesia Tbk. The population in this study was 38 years, namely 1982-2020, based on the purposive sampling method, a sample of 15 years was obtained, namely 2006-2020. In this study, the data were processed using SPSS with data analysis techniques consisting of: (1) Classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test; (2) Multiple linear regression analysis; (3) Correlation and Determination Coefficients; (4) Partial Test; and (5) Simultaneous Test. The hypothesis testing method uses a significance level of 5%. The results showed that the Earning Per Share variable had a partially significant effect on stock prices, the Current Ratio variable had no partially significant effect on stock prices, the Return On Equity variable had no partial significant effect on stock prices, and Earning Per Share, Current Ratio, and Return On Equity does not simultaneously have a significant effect on stock prices.